Anopheles sampling collections in the health districts of Korhogo (Côte d’Ivoire) and Diébougou (Burkina Faso) between 2016 and 2018 - Zogo, Barnabas; Soma, Dieudonné, Diloma; Alou, Ludovic, Ahoua; Mouline, Karine; Dabiré, Roch, Kounbobr; Koffi, Alphonsine, Amanan; Pennetier, Cédric (My University, 2023)
Characterizing the entomological profile of malaria transmission at fine spatiotemporal scales is essential for developing and implementing effective vector control strategies. Here, we present a fine-grained dataset of Anopheles (Diptera: Culicidae) mosquitoes resulting from a series of collections in 55 villages of the rural districts of Korhogo (Northern Côte d'Ivoire) and Diébougou (South-West Burkina Faso) between 2016 and 2018. In the framework of a randomized controlled trial, Anopheles mosquitoes have been periodically collected by Human Landing Catch inside and outside households, and analyzed individually to identify genus and - for a subsample - species, insecticide resistance genetic mutations, plasmodium falciparum infection using molecular tools, and parity status. Overall, more than 3000 human-nights of collection were performed, representing a total sampling effort of approximately 45000 hours. More than 60000 anopheles were collected (mainly An. gambiae s.s., An. coluzzii, and An. funestus). The data are published as a Darwin Core archive in the Global Biodiversity Information Facility - France, comprising 4 files (events, occurrences, mosquito characterizations, and environmental data).
Keywords: Anopheles; burkina faso; collections; cote d'ivoire; data paper; GBIF; human biting rate; human landing catch; malaria; rural; sampling